Autonomy as Core of Creativity and Compliance: Moderated Moderation Model of Maternal Parenting Behaviors. Issue 1 (2nd January 2019) - Wang, Zhengyan; Dong, Shuyang
Abstract : Autonomy is one of the core motivators of children's creativity and (non)compliance. But it is less known how children's (non)compliance links to later creative potential and how maternal parenting behaviors contribute to those links. This article, as part of a longitudinal study, tested whether preschoolers' committed compliance and self-assertion related to their potential for motor creativity and how maternal autonomy-supporting and relatedness-supporting behaviors predicted those relations. Eighty-two Chinese children (32 boys) and their families were included. At 38 months, committed compliance and self-assertion were coded from a cleanup task. Maternal autonomy-supporting and relatedness-supporting behaviors were coded from two 5-min mother-child free-plays. At 60 months, the Thinking Creativity in Action and Movement test (TCAM) was used to measure children's potential for motor creativity. Results showed that after controlling for gender and receptive language, the 38-month-olds' committed compliance negatively, and self-assertion positively, linked to creative potential at 60 months. Moderation analyses revealed that the association between self-assertion and creative potential was strengthened by maternal autonomy-supporting behavior. This moderating effect, however, was weakened by maternal relatedness-supporting behavior. But maternal parenting behaviors did not moderate the association between committed compliance and creative potential. The limitations of this study were discussed.